Effects of lipid composition on the structural properties of human serum amyloid A in reconstituted high-density lipoprotein particles. (July 2019) - Takase, Hiroka; Tanaka, Masafumi; Nakamura, Yuki; Morita, Shin-ya; Yamada, Toshiyuki; Mukai, Takahiro
Highlights: Changes in HDL lipid composition are believed to influence SAA structure and function. SAA-HDL particles with varying lipid compositions were successfully reconstituted. Biophysical and biochemical methods were used to evaluate the effect of rHDL lipid compositions on SAA conformation. The structural properties of SAA were affected by changes in HDL lipid composition. HDL lipid composition may affect the pathogenesis of SAA-related diseases. Abstract: Serum amyloid A (SAA) is a member of exchangeable apolipoproteins that predominantly exists as a component of high-density lipoproteins (HDL). During inflammation, SAA displaces apolipoprotein A–I from HDL and becomes the major protein constituents of HDL. In addition, HDL lipid composition is altered in response to inflammation, which may induce the structural reorganization of SAA and affect its function. Therefore, the physiological roles of HDL can be influenced by changes in their protein and lipid compositions that are triggered by inflammatory diseases. Here, the effect of HDL lipid composition on the structural properties of SAA was examined. Uniformly sized reconstituted HDL (rHDL) was prepared and mainly composed of phosphatidylcholine with a single additional lipid species. Results showed that changes in lipid composition had no significant impact on the helical content of SAA and its thermodynamic stability. However, rHDL lipid composition affected other structural properties of SAA, such as its tryptophan microenvironment and kinetic stability, and thus influenced the susceptibility of SAA to enzymatic digestion. Therefore, changes in HDL lipid composition may affect the physiological function of SAA and the pathogenesis of SAA-related diseases.